Isolation of intestinal mononuclear cells: factors released which affect lymphocyte viability and function. Issue 1 (January 1985) - Gibson, P R; Hermanowicz, A; Verhaar, H J; Ferguson, D J; Bernal, A L; Jewell, D P
Abstract : Whether toxic or immunomodulatory factors are released during the collagenase digestion phase of the isolation of mononuclear cells from human intestinal mucosa was investigated by assessing the effect of the collagenase supernatant on the viability and natural killer activity of normal peripheral blood mononuclear cells. Three hours' incubation in collagenase supernatant suppressed natural killer activity by 25 +/- 4% and decreased the viability of peripheral blood mononuclear cells by 11 +/- 2%. The ability of collagenase supernatants to kill 51Cr-labelled peripheral blood mononuclear cells over four hours was assessed in 16 collagenase supernatants, eight of which produced lysis of 20 +/- 4%. There was no ultrastructural evidence of early degenerative changes in the viable intestinal mononuclear cells fresh from the isolation process or in peripheral blood mononuclear cells incubated in collagenase supernatant. Because prostaglandins are known to inhibit natural killer activity, PGE was measured in 20 collagenase supernatants by radioimmunoassay and found to be high at 27.5 +/- 4.0 ng/ml. Addition of indomethacin to the collagenase medium, however, failed to abolish the inhibitory effect of collagenase supernatant on natural killer activity and did not increase the natural killer activity of isolated intestinal mononuclear cells. The release of cytotoxic and immunomodulatory factors during the isolation of intestinal mononuclear cells indicates the necessity for careful assessment of the potential effects of the isolation process on any function being examined and casts doubt upon the relationship between in vitro findings and in vivo functional capabilities.